Loss of residual cyanogens in a cassava food during storage - Onabolu, A.; Oluwole, O.; Bokanga, M. (Informa UK Limited, 2002)
Residual cyanogens in gari, the most popular cassava food in West Africa, is implicated in the causation of tropical ataxic neuropathy. Gari is eaten by soaking its granules in cold water or by adding boiling water to make a food called eba. This study was conducted to determine whether loss of the residual cyanogens in gari during short-term storage and when gari is made into eba will reduce dietary cyanide load in consumers. Fifteen samples of gari, nine roasted from cassava mash fermented for at least 4 days (type A) and six roasted from cassava mash fermented for only 1 day (type B), were stored for 4 weeks. Free cyanide, linamarin, and cyanohydrin in gari and in eba made from the gari were determined at weekly intervals for 4 weeks. Free cyanide was absent in all samples of gari. Mean cyanohydrin dropped from 8.4 mg HCN Eq/kg dry weight to 4.6 mg HCN Eq/kg dry weight in type A gari, while it dropped from 3.0 mg HCN Eq/kg dry weight to 1.3 mg HCN Eq/kg dry weight in type B gari. Mean linamarin dropped from 6.6 mg HCN Eq/kg dry weight to 2.8 mg HCN Eq/kg dry weight in type A gari, while it dropped from 1.7 mg HCN Eq/kg dry weight to 0.4 mg HCN Eq/kg dry weight in type B gari. Loss of linamarin and cyanohydrin was significant at P < 0.001 for type A gari and at P < 0.002 for type B gari when the weekly levels were compared with initial values. When gari was made into eba, 36% of cyanohydrin and 47% of linamarin were lost from type A gari, while 38% of cyanohydrin and 5% of linamarin were lost from type B gari. Loss of linamarin and cyanohydrin when gari was made into eba was significant for both types of gari at P < 0.001. This study shows that the loss of cyanohydrin and linamarin in gari during short-term storage and when gari is made to eba will reduce dietary cyanide load in consumers